Thermal design and constrained optimization of a fin and tube heat exchanger using differential evolution algorithm - Afsharzadeh, Nader (Strojniški vestnik, 2025)
Fin and tube heat exchangers (FTHEs) are utilized for gas-liquid applications frequently. In the current study, a differential evolution (DE) algorithm and JDE as its variant, with ?-level constraint-handling technique, are effectively applied to optimize an FTHE. Total weight and total annual cost are selected as objective functions. Seven design variables are taken into consideration: outside tube diameter, transverse pitch, longitudinal pitch, fin pitch, number of tube rows, height, and width of shape. Meanwhile, the logarithmic mean temperature difference (LMTD) method is used for heat transfer analysis under identical conditions such as mass flow rate, inlet and outlet temperatures, heat duty, and other thermal properties. The research findings indicate that the implementation of the DE algorithm coupled with ?-level comparison method on optimization problems leads to better solutions for both objective functions compared with those achieved by other approaches such as the genetic algorithm (GA) and heat transfer search (HTS) algorithm. In addition, a parametric analysis is performed for design parameters at the optimum points to show the effects on the objective functions and to identify the feasible design space. The proposed method is straightforward and can generally be employed for thermal design and optimization of FTHEs as well as any other type of compact heat exchangers (CHEs) under different specified duties.
Keywords: cevno rebrasti prenosnik toplote; constrained optimization; diferencialni evolucijski (DE) algoritem; differential evolution (DE) algorithm; fin and tube heat exchanger; optimizacija z omejitvami; skupna teža; skupni letni strošek; termodinamična zasnova; thermal design; total annual cost; total weight